Beyond the farmhand: the role of household head and plot manager in explaining the gender yield gap in Zambia - Mulungu, Kelvin H.; Benny Kabwela (Springer, 2025)
This study examines the intersecting roles of household headship and plot management in Zambia's maize production systems. Unlike the binary gender comparisons in previous research, we investigate productivity differences across four categories: male plot managers in male-headed households (MM), female plot managers in male-headed households (MF), male plot managers in female-headed households (FM), and female plot managers in female-headed households (FF). Using nationally representative data from the 2015 Rural Agricultural Livelihoods Survey (RALS), a Blinder–Oaxaca decomposition framework is used to analyze both the explained and unexplained components of yield gaps between these categories. Results reveal a hierarchy of productivity, where male plot managers in male-headed households achieve the highest yields, followed by female plot managers in female-headed households, female plot managers in female-headed households and lastly female managed plots in male-headed households. The yield gap between the MM and FF plots (64%) is explained by observable factors, including differential access to improved seeds, fertilizers, and extension services. However, gaps involving other combinations, particularly between MM and FM plots (70%), are largely attributed to unobservable factors, such as social norms and institutional constraints. Notably, male plot managers in FF face significant productivity constraints that challenge the assumption of uniform male advantage in agricultural production. We demonstrate that household headship significantly mediates the relationship between gender and agricultural productivity through its influence on resource access and decision-making. These findings suggest that policy interventions aimed at closing gender yield gaps must consider both household structure and plot-management arrangements, moving beyond traditional gender targeting to address the complex intersections between gender and household dynamics in agricultural production systems.